Exploring moral algorithm preferences in autonomous vehicle dilemmas: an empirical study - Sui, Tingting (Frontiers in Psychology, 2023)
The emergence of autonomous vehicles (AVs) engenders numerous ethical dilemmas, primarily centered around their decision-making algorithms. One such ethical quandary, often dubbed the "Trolley problem," necessitates the formulation of moral algorithms grounded in ethical principles for its resolution. To explore this question, we conducted an online survey among 460 participants in China, including 237 females and 223 males, spanning an age range from 18 to 70. The survey was adapted from Joshua Greene's trolley dilemma survey, using Yes/No options to examine participants' choices and Likert scales to measure moral acceptance. The aim was to evaluate participants' inclinations toward four distinct algorithmic strategies — Utilitarianism, Rawlsianism, Egoism, and a Hybrid approach in scenarios involving AVs. Our findings revealed a significant disparity between participants' preferences in scenarios related to AV design and those focused on purchase decisions. Notably, over half of the respondents expressed reluctance to purchase AVs equipped with an "egoism" algorithm, which prioritizes the car owner's safety. Intriguingly, the rejection rate for "egoism" was similar to that of "utilitarianism," which may necessitate self-sacrifice. The hybrid approach of combining "Utilitarianism" and "Egoism" received the highest endorsement, emphasizing the need to balance self-sacrifice and harm minimization in AV moral algorithms. These insights are essential for the ethical and practical development of AV technology in the continually evolving realm of autonomous vehicles.